2015
DOI: 10.1093/bioinformatics/btv634
|View full text |Cite
|
Sign up to set email alerts
|

EMDomics: a robust and powerful method for the identification of genes differentially expressed between heterogeneous classes

Abstract: Motivation: A major goal of biomedical research is to identify molecular features associated with a biological or clinical class of interest. Differential expression analysis has long been used for this purpose; however, conventional methods perform poorly when applied to data with high within class heterogeneity.Results: To address this challenge, we developed EMDomics, a new method that uses the Earth mover’s distance to measure the overall difference between the distributions of a gene’s expression in two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 39 publications
(36 reference statements)
0
64
0
Order By: Relevance
“…Due to technical limitations, scRNAseq data generally have low library sizes resulting in a large fraction of 'dropout' events as well as huge heterogeneity, which introduces a major challenge in identification of DEGs. Given the special characteristics, many new methods have been developed especially for DE analysis of scRNA-seq data [57][58][59][60]. A few studies have compared DEG analysis tools for scRNA-seq data and found that existing methods for analysis of bulk RNA-seq data perform as well as, or not worse than, those specifically developed for scRNA-seq data in terms of the power and FDR [52,61].…”
Section: Discussionmentioning
confidence: 99%
“…Due to technical limitations, scRNAseq data generally have low library sizes resulting in a large fraction of 'dropout' events as well as huge heterogeneity, which introduces a major challenge in identification of DEGs. Given the special characteristics, many new methods have been developed especially for DE analysis of scRNA-seq data [57][58][59][60]. A few studies have compared DEG analysis tools for scRNA-seq data and found that existing methods for analysis of bulk RNA-seq data perform as well as, or not worse than, those specifically developed for scRNA-seq data in terms of the power and FDR [52,61].…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell RNA sequencing is becoming popular in recent years to better understand the stochastic process and gene regulations in a granular resolution (13,15,16,39). The commonly used gene differential expression analysis in single-cell RNA sequencing can be classified into two categories, with one category modeling excess zeros (SCDE, MAST, scDD, DEsingle, and SigEMD) (40)(41)(42)(43)(44) and the other category without modeling the excess zeros in the single-cell RNA sequencing data (DESeq2, SINCERA, D 3 E, EMDomics, Monocle2, Linnorm, and Discriminative Learning) (12,27,(45)(46)(47)(48)(49)(50). DESeq2 is a popular method used for bulk RNA sequencing data analysis, which is also often used for analyzing single-cell RNA sequencing data for testing of differential expression between groups.…”
Section: Statistical Methods For Single-cell Rna Sequencing Differentmentioning
confidence: 99%
“…EMDomics detects significantly differentially expressed genes between groups for single-cell RNA sequencing data by comparing the two distribution functions of gene expressions between groups (48). EMDomics compares the differences between groups based on EMD, a commonly used approach to compare two histograms in imaging analysis.…”
Section: Emdomicsmentioning
confidence: 99%
“…One of the more common applications of RNA-seq data is estimating and testing for differences in gene expression between two groups. Many packages and techniques exist to perform this task [Robinson and Smyth, 2007b, Hardcastle and Kelly, 2010, Van De Wiel et al, 2012, Kharchenko et al, 2014, Law et al, 2014, Love et al, 2014, Finak et al, 2015, Guo et al, 2015, Nabavi et al, 2015, Delmans and Hemberg, 2016, Korthauer et al, 2016, Costa-Silva et al, 2017, Qiu et al, 2017, Miao et al, 2018, Van den Berge et al, 2018, Wang and Nabavi, 2018, Wang et al, 2019, and so developing approaches and software to compare these different software packages would be of great utility to the scientific community. Generating data from the two-group model is a special case of (1) and (2), where…”
Section: Application: Evaluating Differential Expression Analysismentioning
confidence: 99%